The Influence of Organizational Culture, Employee Loyalty, and Employee Commitment on Leadership Style at Higher Education Institutions - Yesi Elfisa; Leni Marlina; Yohanes Yohanes; Saukani Saukani; M. Jainuri (Siber Nusantara of Community Service Review, 2024)
The Effect of Organizational Culture, Employee Loyalty and Employee Commitment on Leadership Style is a scientific publication that falls within the scope of a literature review in the scientific domain. The purpose of this article is to develop hypotheses about the relationship between factors that will be applied in future research. Research items are found on academic internet media such as Mendeley, Google Scholar, and online libraries. Electronic journals and open access e-books are sources of research methodology used in the research library. The results of this research: 1) Organizational Culture affects Leadership Style; 2) Employee Loyalty affects Leadership Style; and 3) Employee Commitment affects Leadership Style.